The individual and the city: Two models of interaction - Malakhov, Sergey; Repina, Eugenia (project baikal, 2024)
Two conditionally opposite types of human interaction with society are considered: extroverted and introverted. The process of extroverted interaction is aimed at direct contact with the urban community, and introverted – at the imaginary reality, the artistic image of what is happening. The first type is supported by the majority cultural practice and the rules of the system, while the second type is associated with a minimal presence in the system and a playful interpretation of the context. The key elements of architectural interpretation of the interaction under consideration are the house and the city – simultaneously as real objects and as metaphors of opposite meanings. Architecture in its essential manifestation is embodied as a city in the extroverted project, and as a house in the introverted one.
Keywords: city and house; extroverted/introverted; communication/solitude; city code; geometric patterns; planning grid; living room/labyrinth